Keabsahan Pembuktian Perkara Pidana pada Persidangan Online Selama Masa Pandemi Covid-19 - Aditya Cahya Adyaksana Putra; Laras Astuti (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
The high number of COVID-19 cases has had a multidimensional impact starting from the economy entering a wave of recession. In Indonesia, the government has implemented Physical Restrictions and Work From Home policies with the aim of reducing the risk of the spread of COVID-19. This policy also applies at the court level where the implementation of judicial hearings in the judicial room directly or through e-court because a direct trial has the potential to cause crowds and create new clusters of Covid-19 transmission. This study aims to identify and analyze legal remedies for the validity of evidence in criminal cases in online trials during the COVID-19 pandemic. This research is a normative research. Normative legal research is legal research that uses sources obtained from literature studies. Normative legal research includes research on legal principles, clinical legal research, legislation, legal history and comparative law. The results show that the validity of evidence in criminal cases can be seen based on two things, first from the theoretical side of the validity of evidence in criminal cases through legal teleconferences because Indonesia adheres to the theory of a negative proof system where in addition to evidence referring to the law, it also places the judge's conviction in seeking material truth. Second, from a juridical point of view, it can be narrowed down, namely the evidence in criminal case trials via teleconference during the COVID-19 pandemic is legally valid because first the debate over Article 185, there are rules outside the Criminal Procedure Code that regulate electronic evidence and the condition of the COVID-19 pandemic requires the state to prioritize safety. citizens but must continue to carry out the criminal justice process.